Features of immunohistochemical markers of stem CELLS CD-117, CD-44 in female placentas on the background of chronic stress - Y.M. Bondarenko (Publishing House TRILIST, 2022)
Background. Placenta is a subject of interest to a wide range of scientists because it is rich in stem cells and their precursors. A stem cell is a cell that has the ability to self-repair and can differentiate into offspring (daughter cells) of one or more germ layers. In recent years, scientists have obtained new data of stem cells regenerative potential. However, only isolated publications about placental stem cells are available. Therefore, our studies about placental stem cells are important for discovery of structural and molecular mechanisms, their changes under the influence of chronic stress. Objective: to study the features of immunohistochemical markers of pluripotent stem cells and their morphological features. Materials and methods. We examined 80 women placentas with chronic stress in comparison with control using general histological and immunohistochemical methods in the following groups: group 1 - women placentas with physiological course of pregnancy in term 38-40 weeks, group 2 - women placentas with miscarriage, group 3 - women placentas with chronic stress due to internal irradiation (4.5 Bq/kg and more), group 4 - women placentas which had COVID-19 during pregnancy. Results. There was a significant increase of stem cell markers expression in the three study groups with a significant predominance in groups 3 and 4. It was also determined the different direction of their active factors. Conclusions. The general changes of all structures of the placental barrier are detected as a result of chronic stress due to various factors: micro detachment of the decidual membrane (significant increase in cases in the studied groups); malperfusion in the structures of the maternal placental barrier; in the placenta stem cells of the three study groups in comparison with the control were found stress markers. Thus, chronic stress due to various factors causes the same type of changes in placental structures, but they have different degrees of expression - with internal irradiation doses ≥ 4.8 Bq/kg, these changes are most expressive.